INFRASTRUCTURE DEVELOPMENT AND ITS IMPACT ON SDG 9 IN UZBEKISTAN'S LOGISTICS SECTOR - Abdumalik Erkinovich Soliyev; Samariddin Makhmudov (Antis Publisher, 2024)
This paper examines the role of infrastructure development in advancing Sustainable Development Goal (SDG) 9, which focuses on industry, innovation, and infrastructure, within Uzbekistan's logistics sector. It explores the current state of logistics infrastructure, including transportation networks, warehousing, and digital technologies, and discusses the challenges and opportunities associated with infrastructure improvements. The paper highlights how enhanced infrastructure can boost efficiency, reduce costs, and support economic growth, while also promoting sustainable practices. It concludes with recommendations for policymakers and industry stakeholders to prioritize infrastructure investments that align with sustainable development objectives.